Teaching knowledge within the scope of the Universidade Aberta do Brasil (UAB) system (Revista Contexto & Educação, 2024)
The objective of this article is to investigate the constitution of the knowledge base for teaching of teachers who work or have worked in distance education within the scope of the Universidade Aberta do Brasil (UAB System). The research made use of methodological triangulation, which involves multiple methods, sources of collection and forms of analysis. In particular, data were collected through virtual questionnaires with 677 teachers. Subsequently, semi-structured interviews were carried out with 8 professionals. The analysis used quantitative and qualitative approaches. About the results, the research identifies that the knowledge of teachers come from different sources, namely: professional experience, peer relationships, research in the area, etc. In addition, the knowledge base for teaching comprises content, pedagogical and technological knowledge, as well as the amalgamation constituted by the intersection between them. Therefore, the technological pedagogical content knowledge is important to understand the teaching performance in distance education.
Keywords: Distance education; teaching knowledge; knowledge base for teaching; Universidade Aberta do Brasil System